Evaluasi Pengolahan Air Limbah Rumah Sakit X - Kancitra Pharmawati; Ghifari Salman R (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
One of the wastes generated by hospitals is liquid waste. Liquid waste that is harmful to the environment. Evaluation of the RS X wastewater management plant to determine whether the wastewater treatment is appropriate and the wastewater produced by the hospital that is discharged into the water body is safe for the environment. The research was conducted at a private hospital in Bandung Regency. The type of research used is observation with a descriptive approach. The evaluation was carried out by comparing the existing conditions of WWTP influent and effluent with the quality standards of the Minister of Environment and Forestry Regulation No. 68 of 2016. Wastewater discharge in September, October and November were 390 m3 / month, 381 m3 / month and 648 m3 / month. The results of the study found that the influent characteristics of wastewater are biodegradable with a BOD / COD ratio of 0.31, influent wastewater namely BOD, COD, TSS and oil & grease exceeds the standard. In the equalization basin unit, biofilter tank, oxidation tank, filter and indicator pond there are still those that do not meet the design criteria, but the treatment results in the WWTP the quality of the parameters BOD, COD, TSS and oil & grease do not exceed the standard with consecutive levels of 8.04 mg/L, 25.14 mg/L, 10 mg/L, <1.61 mg/L.